Revalidación del método analítico por espectrofotometría para la cuantificación de mebendazol en tabletas - Gutiérrez Castro, Jhemifer Paola (2008)
They determined the parameters for the revalidation of the analytical method spectrophometric to 310 nm (TPT126 review 05), proposed by the Institute laboratory Quimioterápico SA (IQFARMA) for the quantification of Mebendazole tablets. We performed an analysis of Mebendazole 100 mg tablets lot 00101007. Formic acid and alcohol isopropílico were used like solvents. Getting in the trial of Linearity a correlation coefficient of 0.9999; Test Statistical Linearity and Response Factor, expressed conformity. For accuracy, the percentage of recovery was 100,885. In the Test G Cochran was obtained G Exp. Tables G minor (0.4993 <0.8709). For statistical Student's t test was obtained t Exp. Less than t Table (2,169 <2,306), the accuracy is correct according to their respective specifications. In assessing accuracy, repeatability of the test showed a concentration averaged 101,344 mg per tablet with a DSR of 0,206. In the intermediate Accuracy The coefficient of variation between the average values of an analyst and the other was 0,271%, being acceptable to the restoration. The method used in this report proved to be specific in determining the analyte between excipients, the samples were subjected to degradation by UV getting 100,036% for the irradiated sample and 100,096% for the non-irradiated sample. Validate certain parameters can be given as to revalidated analytical method TPT126 review 05 proposed by the Institute laboratory Quimioterápico SA (IQFARMA) for the quantification of Mebendazole tablets